Corporate social responsibility and corporate image of Telkom SA SOC Limited - Nevondo, Immanuel Mboniseni (University of the Witwatersrand, Johannesburg, 2024)
State-owned enterprises are organisations owned by the government and they operate within government regulations. There are different factors that these organisations are obligated to account for in daily operations when making decisions; these factors define how state-owned enterprises (SOEs) differ from the private corporations in building their corporate image. The SOEs’ environment remains in distress as the public regularly complain about their levels of service delivery and do not trust the SOEs, due to their perceived bad image. However, South African SOEs have the obligation to create special economic and social zones to improve the lives of South Africans. Purpose The use of corporate image in the private sector is increasing significantly, as it is a driver of brand loyalty, and scholars are increasingly researching branding using various theoretical frameworks. The purpose of this study is to research the impact of corporate reputation as a mediator of corporate image for a state-owned enterprise (SOE). Further, the research assesses the indirect impact of corporate social responsibility on SOE corporate image and examines other major dependable variables that may have an influence relationship on corporate reputation. Design/methodology/approach To assess the study, a quantitative research method was employed, using the data obtained from Telkom customers; questionnaires were sent to individuals, using an electronic self-administered close-ended questionnaire. The data of a hundred and ninety (190) valid responses were analysed using SEM AMOS 28 and SPSS 28. Findings The outcome of the study revealed that out of nine hypotheses tested, five hypotheses were found insignificant and not supported, while the remaining four were significant and supported. Practical implications It is important for the company to priorities its service quality and marketing factors to align them with the corporate reputation, and corporate image by means of the company’s corporate social responsibility efforts. By focusing on this area, the company can enhance its corporate image, ii reputation, and stakeholder perception, ultimately contributing to the long-term sustainability of the business. Companies should reassess their CSR initiatives to ensure they align with stakeholders' expectations and contribute meaningfully to corporate reputation building. Originality The study contributes to understanding the impact of service quality dimensions, marketing factors and corporate reputation on corporate image. Corporate image, as a dependent variable, is influenced by different variables, including dimensions of service quality, such as reliability, responsiveness, assurance and empathy, marketing factors, namely, CSR, advertising exposure, social media marketing activities and website quality. Corporate repution plays a mediating role between these variables.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Strategic Marketing to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: State owned entities (SOE); Service quality; Corporate image (CI); Corporate social responsibility (CSR); UCTD; SDG-8: Decent work and economic growth